CALABAI DAN BISSU SUKU BUGIS: REPRESENTASI GENDER DALAM NOVEL CALABAI KARYA PEPI AL-BAYQUNIE - Rokhmansyah, Alfian; Hanum, Irma Surayya; Dahlan, Dahri (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2018)
This study aims to describe the life of calabai and bissu, as well as the views of the people depicted in the Calabai novel by Pepi Al-Bayqunie. This research is library research with a qualitative approach. Data analysis was carried out through several stages, namely the data classification stage, data analysis, and the conclusion of the analysis results. The results of this study indicate that calabai and bissu are gender variations other than men and women in Bugis culture as illustrated in the Calabai novel by Pepi Al-Bayqunie. Calabai who was described by the author in the novel was a Calabai who had privileges and finally he became a bissu. In relation to the existence of calabai and bissu as illustrated in the novel, it turns out that there is a rejection from the group who consider these two gender variations to be incompatible with human nature. The existence of calabai is a problem because it is contrary to the social construction that already exists in the community. However, unlike calabai, the existence of bissu is considered more respectable because it plays an important role in Bugis culture.